Does viral circulation in slums have a global impact? The lesson learned from SARS-CoV-2 circulation in Complexo de favelas da Maré, Rio de Janeiro, Brazil - dos Santos, Monique Cristina; Fintelman-Rodrigues, Natalia; Silva, Aline de Paula Dias da; Silva, Rodolfo Leandro Nascimento; Seixas, Victor Corrêa; Batista-da-Silva, Amanda A.; Ferreira, Marcelo Alves; Bozza, Patrícia T.; Bozza, Fernando A.; Souza, Thiago Moreno L. (Frontiers in Microbiology, 2025)
Because of growing inequalities, more than one-third of the worldwide population is expected to live in slums by 2050. Although slum dwellers are at increased risk of infectious diseases, this population may have been overlooked with respect to the sustainability of virus evolution. In this study, we aimed to analyze the genetic diversity and evolution of SARS-CoV-2 in the Complexo de Favelas da Maré slum, Rio de Janeiro, Brazil, and assess its impact on the global spread of the virus. We found that this slum harbored multiple strains of SARS-CoV-2, and its amplification and genetic diversity connected with the global circulation from 2020 to 2022. Thus, enhancing surveillance in slums could be important for future epidemic/pandemic preparedness by connecting virus genetic diversity in this region with its circulation at divergent locations.